2014
DOI: 10.1007/s00294-014-0425-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial D-loop and Cytochrome Oxidase C subunit I polymorphisms among the breast cancer patients of Mizoram, Northeast India

Abstract: Mitochondrial DNA (mtDNA) is known for its high frequencies of polymorphisms and mutations as it is prone to oxidative stress. The aim of the present study is to assess the novel mutations in mitochondrial genes from blood samples among the breast cancer patients from a less studied Northeast Indian population. D, B, L haplogroups were observed in the cancer samples and a total of 44 mtDNA D-loop sequence variations at 42 distinct nucleotide positions were found. All the sequence variations were transitional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
0
15
0
2
Order By: Relevance
“…The study design and data collection methods have been described in detail previously [24]. For this study, a total of 62 gastric cancer (GC) patients with or without a family history of cancer (median age 58 years; range 37–79) who received treatment between September 2012 and February 2014 at Agartala Govt.…”
Section: Methodsmentioning
confidence: 99%
“…The study design and data collection methods have been described in detail previously [24]. For this study, a total of 62 gastric cancer (GC) patients with or without a family history of cancer (median age 58 years; range 37–79) who received treatment between September 2012 and February 2014 at Agartala Govt.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with gastric neoplasms including adenocarcinoma (MALT lymphoma, stromal, or carcinoid tumors) were included. Patients with secondary or recurrent GC, previous history of other malignancies, or refusal to participate were excluded from the study . Medical charts were reviewed using a standard protocol to obtain information on cancer treatment, clinical stage, dietary habits, previous disease history, physical activity, tobacco, and alcohol use by an in‐person interview using a structured questionnaire .…”
Section: Methodsmentioning
confidence: 99%
“…Patients who were histopathologically confirmed as breast adenocarcinoma were selected for this study. Demographic data and family history for BC were collected by a structured questionnaire administered by trained personnel as previously described (Ghatak et al 2014). One ml of peripheral blood was collected from each patient including 10 control samples (HC) from healthy volunteers with no previous history of breast cancer and matched by gender, age (±5 years) and area of residence with the cancer patients.…”
Section: Subjectsmentioning
confidence: 99%
“…Mizoram belonging to North Eastern state of India has a high agestandardised breast cancer rate of 14.1 per 1,00,000 population (NCRP 2013). Studies have shown that consumption of alcohol, tobacco and peculiar food habits, especially high fat intake, are important risk factors for breast cancer (Ghatak et al 2014;Sieri et al 2008).…”
Section: Introductionmentioning
confidence: 97%